Polyacrylate pressure-sensitive adhesive tape for improving structural strength of lithium battery and preparation method thereof
By using polyacrylate pressure-sensitive adhesive coated on a heat-shrinkable substrate layer in lithium batteries, the existing expandable tape's problems of easy degumming and poor stability are solved, and the structural strength of the lithium battery is improved and the roller test pass rate is improved. improvement.
Patent Information
- Application Number
- CN202410328954.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-21
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-03-21
AI Technical Summary
The existing expandable tape is prone to degumming in lithium batteries, has poor stability, and insufficient expansion effect, making it difficult to improve the structural strength of lithium batteries and the passing rate of drum tests.
The heat-shrinkable base material layer is coated with a unique polyacrylate pressure-sensitive adhesive, which has excellent aging resistance, electrolyte resistance, peeling force and thermal stability. With the expansion effect of the heat-shrinkable base material layer, it enhances the Structural strength of lithium batteries.
It improves the structural strength of lithium batteries and the roller test pass rate of cylindrical batteries, and enhances the safety performance and usability of batteries.
Smart Images

Figure CN118206933B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyacrylate pressure-sensitive adhesive tapes for lithium batteries, and in particular to a polyacrylate pressure-sensitive adhesive tape for improving the structural strength of lithium batteries and a preparation method thereof. Background Art
[0002] Lithium battery tape refers to a pressure-sensitive adhesive tape used for electrode winding, pole piece protection and core termination in the middle production process of lithium battery cells (winding / stacking, shell welding and sealing, etc.). Its main function is to insulate and fix the lithium battery.
[0003] Usually, cylindrical lithium batteries need to undergo a roller drop test to evaluate whether the battery can work normally during the drop process and whether there will be no safety problems such as rupture, leakage, and explosion. The finished cylindrical lithium battery is subjected to a roller test, and the voltage and internal resistance change rate before and after the roller test are compared. When the voltage or internal resistance change rate exceeds 25% after the roller test, it is considered a failure, otherwise it is considered a pass, and the percentage of batteries that pass is counted to meet factory requirements. Application No. 202310305784.8 discloses a method for improving the pass rate of a cylindrical battery roller test, using an expandable tape to fill the gap between the roll core and the steel shell wall to prevent the roll core and the steel shell wall from relative displacement during the roller test, avoiding the positive and negative ears of the connecting device from being broken by force, and improving the roller test pass rate of the cylindrical battery, thereby improving the safety performance and performance of the battery; however, the existing expandable tape, when used in cylindrical batteries, is easy to debond, has poor stability, and has insufficient expansion effect, making it difficult to improve the structural strength of the lithium battery and improve the pass rate of the lithium battery roller test. Summary of the invention
[0004] In order to overcome the shortcomings and deficiencies in the prior art, the purpose of the present invention is to provide a polyacrylate pressure-sensitive adhesive tape for improving the structural strength of lithium batteries. A unique polyacrylate pressure-sensitive adhesive is coated on a heat-shrinkable substrate layer. The heat-shrinkable substrate layer will shrink and expand in an electrolyte. Under the cooperation of the unique polyacrylate pressure-sensitive adhesive, the expansion effect of the heat-shrinkable substrate layer is better. The unique polyacrylate pressure-sensitive adhesive has excellent aging resistance and electrolyte resistance, and has good peeling force and thermal stability, which is more conducive to improving the structural strength of lithium batteries and improving the pass rate of cylindrical battery roller tests.
[0005] Another object of the present invention is to provide a method for preparing a polyacrylate pressure-sensitive tape for improving the structural strength of a lithium battery. The preparation method is simple to operate, convenient to control, high in production efficiency, low in production cost, and can be used for large-scale production.
[0006] The object of the present invention is achieved by the following technical scheme: A polyacrylate pressure-sensitive adhesive tape for improving the structural strength of a lithium battery, comprising a heat-shrinkable substrate layer, and a polyacrylate pressure-sensitive adhesive coated on one side of the heat-shrinkable substrate layer;
[0007] The polyacrylate pressure-sensitive adhesive comprises the following raw materials in parts by weight:
[0008]
[0009] The polyacrylate pressure-sensitive adhesive tape for improving the structural strength of lithium batteries of the present invention adopts a heat-shrinkable substrate layer and a polyacrylate pressure-sensitive adhesive coated on one side of the heat-shrinkable substrate layer, and the polyacrylate pressure-sensitive adhesive adopts a soft monomer, a hard monomer, a functional monomer, a bifunctional epoxy acrylate, an epoxy plasticizer, an initiator, a crosslinking agent, an antioxidant and a diluent. The soft monomer provides basic initial viscosity and copolymerizes with the hard monomer to increase cohesion, thereby ensuring the long-term use of the pressure-sensitive adhesive and facilitating the improvement of the peeling force. In addition, the crosslinking copolymerization modification of the functional monomer improves the peeling force of the pressure-sensitive adhesive, enhances the cohesive strength and the electrolyte resistance, so that the pressure-sensitive adhesive can maintain stable adhesion and performance in an electrolyte environment; the bifunctional resin-epoxy acrylate combines the characteristics of epoxy groups and acrylate groups, so that it exhibits good elasticity, adhesion and aging resistance after crosslinking and curing. chemical properties; the epoxy plasticizer penetrates into the molecular chains of the pressure-sensitive adhesive, improves the adhesion performance of the pressure-sensitive adhesive, increases its bonding strength and durability, and weakens the interaction between the molecular chains, thereby improving the elasticity and flexibility of the pressure-sensitive adhesive; under the action of the initiator and the cross-linking agent, the soft monomer, the hard monomer, the functional monomer and the difunctional epoxy acrylate initiate polymerization and cross-linking reaction to form a stable cross-linked network structure, thereby improving the heat resistance, adhesion and cohesive strength of the pressure-sensitive adhesive, and enhancing its electrolyte resistance, effectively ensuring the long-term adhesion and elasticity of the pressure-sensitive adhesive, and at the same time, it is beneficial to improve the difunctional epoxy acrylate and epoxy plasticizer to synergistically enhance the elasticity and flexibility of the pressure-sensitive adhesive, and is more conducive to adapting to the expansion deformation of the heat-shrinkable substrate layer, thereby improving the expansion effect of the heat-shrinkable substrate layer, and is more conducive to improving the structural strength of the lithium battery and improving the pass rate of the cylindrical battery roller test. Antioxidants are used to prevent the performance of pressure-sensitive adhesives from deteriorating due to oxidation during storage and use, and to improve the stability and durability of pressure-sensitive adhesives; diluents are mainly used to adjust the viscosity and fluidity of pressure-sensitive adhesives, making them easier to process and use.
[0010] Preferably, the soft monomer is at least one of n-butyl acrylate, isooctyl acrylate, and 2-ethylhexyl acrylate; and the hard monomer is at least one of methyl methacrylate, methyl acrylate, and styrene.
[0011] Preferably, the functional monomer is a mixture of methacrylic acid and glycidyl methacrylate in a weight ratio of 2:3-5.
[0012] By adopting the above technical solution, methacrylic acid has a greater promoting effect on cohesion, but has little effect on adhesion; glycidyl methacrylate plays a key role in improving the electrolyte resistance of the pressure-sensitive adhesive, giving the pressure-sensitive adhesive better electrolyte resistance, so that the pressure-sensitive adhesive can maintain stable adhesion, elasticity and other properties in the electrolyte environment. Methacrylic acid and glycidyl methacrylate work synergistically to further improve the cohesive strength of the pressure-sensitive adhesive, making the pressure-sensitive adhesive less likely to be destroyed or dissolved when in contact with the electrolyte, thereby improving its electrolyte resistance.
[0013] Preferably, the difunctional epoxy acrylate is bisphenol A epoxy acrylate and / or novolac epoxy acrylate.
[0014] The above technical solution combines the characteristics of epoxy groups and acrylate groups, so that it exhibits good elasticity, adhesion and aging resistance after cross-linking and curing; the reaction activity of phenolic epoxy acrylate is higher than that of bisphenol A epoxy acrylate, and the cross-linking density is also greater. More preferably, the difunctional epoxy acrylate is a mixture of bisphenol A epoxy acrylate and phenolic epoxy acrylate in a weight ratio of 1:8-9, which can undergo cross-linking reaction with other components in polyacrylate pressure-sensitive adhesive to form a more stable polymer network. This cross-linking structure helps to improve the cohesive strength and mechanical properties of the pressure-sensitive adhesive, making it more durable and reliable, and can also significantly enhance the resistance of the polyacrylate pressure-sensitive adhesive to the electrolyte, preventing it from experiencing performance degradation or damage when in contact with the electrolyte.
[0015] Preferably, the epoxy plasticizer is at least one of epoxidized soybean oil, epoxy butyl oleate, and epoxy fatty acid octyl ester.
[0016] By adopting the above technical solution, the epoxy plasticizer penetrates between the molecular chains of the pressure-sensitive adhesive, improves the adhesion performance of the pressure-sensitive adhesive, increases its bonding strength and durability, weakens the interaction between the molecular chains, thereby improving the elasticity and flexibility of the pressure-sensitive adhesive, making the pressure-sensitive adhesive more easily adapt to deformation and less prone to cracking or breaking. More preferably, the epoxy plasticizer is a mixture of epoxy oleic acid butyl ester and epoxy fatty acid octyl ester in a weight ratio of 1:1.
[0017] Preferably, the initiator is at least one of benzoyl peroxide, diisopropylbenzene peroxide, azobisisobutyronitrile and dimethyl azobisisobutyrate; the cross-linking agent is aluminum acetylacetonate and / or toluene diisocyanate; the antioxidant is at least two of antioxidant 1010, antioxidant BHT and antioxidant 168; and the diluent is ethyl acetate and / or acetone.
[0018] Furthermore, the cross-linking agent is a mixture of aluminum acetylacetonate and toluene diisocyanate in a weight ratio of 1:5, and reacts with soft monomers, hard monomers, functional monomers or polymer chains to form a more stable and tough polymer network, which helps to significantly improve the cohesive strength, heat resistance, solvent resistance and electrolyte resistance of the pressure-sensitive adhesive. The antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:3.
[0019] Preferably, the preparation method of the polyacrylate pressure-sensitive adhesive comprises the following steps:
[0020] (R1), take soft monomer, hard monomer, functional monomer, difunctional epoxy acrylate, epoxy plasticizer, initiator, crosslinking agent, antioxidant and diluent according to weight parts and set aside;
[0021] (R2), mixing the initiator and the diluent evenly to obtain a diluted initiating solution, and dividing the solution into three portions;
[0022] (R3), mixing the soft monomer, the hard monomer, the functional monomer, the difunctional epoxy acrylate and the first diluted initiator solution evenly, and letting it stand for 3-5 minutes to obtain a prepolymer solution;
[0023] (R4), adding the second portion of the diluted initiating solution to the prepolymer solution at a temperature of 75-80°C and a rotation speed of 300-500 rpm for 2-3 hours, and keeping the temperature for reaction for 1-2 hours to obtain an intermediate product;
[0024] (R5) adding the third portion of the diluted initiating liquid, epoxy plasticizer and crosslinking agent to the intermediate product at a temperature of 85-90°C and a rotation speed of 300-500 rpm, keeping the reaction warm for 1-2 hours, and then adding an antioxidant and mixing evenly to obtain a polyacrylate pressure-sensitive adhesive.
[0025] Wherein, in the step (R2), the diluted initiating liquid is divided into three parts, and the weight ratio of the first diluted initiating liquid, the second diluted initiating liquid and the third diluted initiating liquid is 2-3:3-5:2-4.
[0026] Preferably, the heat shrinkable substrate layer is an oriented polystyrene film; the thickness of the heat shrinkable substrate layer is 37-43 μm, and the thickness of the polyacrylate pressure-sensitive adhesive is 8-12 μm.
[0027] By adopting the above technical scheme, an oriented polystyrene film is coated with a polyacrylate pressure-sensitive adhesive and applied to a lithium battery cell after it is put into a shell. Under high temperature and electrolyte environment, the oriented polystyrene film expands and the heat-shrinkable substrate layer expands better under the cooperation of the unique polyacrylate pressure-sensitive adhesive, which is more conducive to improving the structural strength of the lithium battery and improving the pass rate of the cylindrical battery roller test.
[0028] Another object of the present invention is achieved by the following technical solution: The preparation method of the polyacrylate pressure-sensitive tape for improving the structural strength of lithium batteries comprises the following steps:
[0029] (S1), taking a heat shrinkable substrate layer and a polyacrylate pressure-sensitive adhesive, and setting them aside;
[0030] (S2), performing a surface corona treatment on the heat shrinkable substrate layer to obtain a surface corona heat shrinkable substrate layer;
[0031] (S3), heating the polyacrylate pressure-sensitive adhesive to 35-40° C., preheating for 15-20 min, filtering through a cartridge filter, and coating the polyacrylate pressure-sensitive adhesive on the corona surface of the corona heat shrinkable substrate layer to obtain a semi-finished product;
[0032] (S4), subjecting the semi-finished product to a multi-stage drying treatment and then winding it up to obtain a polyacrylate pressure-sensitive adhesive tape.
[0033] Among them, in step (S3), the polyacrylate pressure-sensitive adhesive is first preheated at a specific temperature and time to ensure that the pressure-sensitive adhesive can be fully softened and enhance fluidity so that it can be evenly and stably coated on the heat-shrinkable substrate layer during the coating process.
[0034] Preferably, the filter pore size of the cartridge filter is 3-5 μm; in the step (S4), the temperatures of each stage of the multi-stage drying treatment are 75-80°C, 88-92°C, 100°C, and 88-92°C, respectively, and the drying time of each stage of the multi-stage drying treatment is 1-2 min.
[0035] The beneficial effects of the present invention are as follows: the polyacrylate pressure-sensitive adhesive tape for improving the structural strength of lithium batteries of the present invention is coated with a unique polyacrylate pressure-sensitive adhesive on a heat-shrinkable substrate layer, and the heat-shrinkable substrate layer will shrink and expand in an electrolyte. Under the cooperation of the unique polyacrylate pressure-sensitive adhesive, the expansion effect of the heat-shrinkable substrate layer is better, and the unique polyacrylate pressure-sensitive adhesive has excellent aging resistance and electrolyte resistance, and has good peeling force and thermal stability, which is more conducive to improving the structural strength of lithium batteries and improving the passing rate of cylindrical battery roller tests.
[0036] The preparation method of the polyacrylate pressure-sensitive adhesive tape of the invention has simple operation, convenient control, high production efficiency and low production cost, and can be used for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a test report diagram of the polyacrylate pressure-sensitive adhesive tape of Example 1 of the present invention for testing its 180° peeling force, initial tack and room-temperature swelling multiple;
[0038] Figure 2 This is a process diagram of the swelling multiple at 85° C. of the polyacrylate pressure-sensitive adhesive tape of Example 3 of the present invention. DETAILED DESCRIPTION
[0039] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments and drawings. The contents mentioned in the implementation modes are not intended to limit the present invention.
[0040] Example 1
[0041] A polyacrylate pressure-sensitive adhesive tape for improving the structural strength of a lithium battery, comprising a heat-shrinkable substrate layer and a polyacrylate pressure-sensitive adhesive coated on one side of the heat-shrinkable substrate layer;
[0042] The polyacrylate pressure-sensitive adhesive comprises the following raw materials in parts by weight:
[0043]
[0044] The soft monomer is a mixture of n-butyl acrylate and isooctyl acrylate in a weight ratio of 3:1; the hard monomer is a mixture of methyl methacrylate and styrene in a weight ratio of 5:2.
[0045] The functional monomer is a mixture of methacrylic acid and glycidyl methacrylate in a weight ratio of 2:4.
[0046] The bifunctional epoxy acrylate is prepared by mixing bisphenol A epoxy acrylate and novolac epoxy acrylate in a weight ratio of 1:9.
[0047] The epoxy plasticizer is prepared by mixing epoxy butyl oleate and epoxy fatty acid octyl ester in a weight ratio of 1:1.
[0048] The initiator is benzoyl peroxide; the cross-linking agent is a mixture of aluminum acetylacetonate and toluene diisocyanate in a weight ratio of 1:5; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:3; and the diluent is a mixture of ethyl acetate and acetone in a weight ratio of 3:1.
[0049] The preparation method of the polyacrylate pressure-sensitive adhesive comprises the following steps:
[0050] (R1), take soft monomer, hard monomer, functional monomer, difunctional epoxy acrylate, epoxy plasticizer, initiator, crosslinking agent, antioxidant and diluent according to weight parts and set aside;
[0051] (R2), mixing the initiator and the diluent evenly to obtain a diluted initiating solution, and dividing the solution into three portions, wherein the weight ratio of the first portion of the diluted initiating solution, the second portion of the diluted initiating solution and the third portion of the diluted initiating solution is 3:4:3;
[0052] (R3), mixing the soft monomer, the hard monomer, the functional monomer, the difunctional epoxy acrylate and the first diluted initiator solution evenly, and letting it stand for 4 minutes to obtain a prepolymer solution;
[0053] (R4), adding the second portion of the diluted initiating solution to the prepolymer solution at 78°C and 500 rpm for 2 hours, and keeping the temperature for reaction for 2 hours to obtain an intermediate product;
[0054] (R5) Add the third diluted initiator solution, epoxy plasticizer and crosslinking agent to the intermediate product at 88°C and 500 rpm, keep the mixture warm for 1 hour, then add antioxidant and mix well to obtain polyacrylate pressure-sensitive adhesive.
[0055] The heat shrinkable substrate layer is an oriented polystyrene film; the thickness of the heat shrinkable substrate layer is 40 μm, and the thickness of the polyacrylate pressure-sensitive adhesive is 10 μm.
[0056] The method for preparing the polyacrylate pressure-sensitive adhesive tape for improving the structural strength of a lithium battery comprises the following steps:
[0057] (S1), taking a heat shrinkable substrate layer and a polyacrylate pressure-sensitive adhesive, and setting them aside;
[0058] (S2), performing a surface corona treatment on the heat shrinkable substrate layer to obtain a surface corona heat shrinkable substrate layer;
[0059] (S3), heating the polyacrylate pressure-sensitive adhesive to 38° C., preheating for 18 min, filtering through a cartridge filter, and coating the polyacrylate pressure-sensitive adhesive on the corona surface of the corona heat shrinkable substrate layer to obtain a semi-finished product;
[0060] (S4), subjecting the semi-finished product to a multi-stage drying treatment and then winding it up to obtain a polyacrylate pressure-sensitive adhesive tape.
[0061] The filter pore size of the cartridge filter is 5 μm; in the step (S4), the temperatures of each stage of the multi-stage drying treatment are 80° C., 90° C., 100° C., and 90° C., respectively, and the drying time of each stage of the multi-stage drying treatment is 1 minute.
[0062] Example 2
[0063] A polyacrylate pressure-sensitive adhesive tape for improving the structural strength of a lithium battery, comprising a heat-shrinkable substrate layer and a polyacrylate pressure-sensitive adhesive coated on one side of the heat-shrinkable substrate layer;
[0064] The polyacrylate pressure-sensitive adhesive comprises the following raw materials in parts by weight:
[0065]
[0066] The soft monomer is a mixture of n-butyl acrylate and isooctyl acrylate in a weight ratio of 3:1; the hard monomer is a mixture of methyl methacrylate and styrene in a weight ratio of 5:2.
[0067] The functional monomer is a mixture of methacrylic acid and glycidyl methacrylate in a weight ratio of 2:3.
[0068] The bifunctional epoxy acrylate is prepared by mixing bisphenol A epoxy acrylate and novolac epoxy acrylate in a weight ratio of 1:8.
[0069] The epoxy plasticizer is prepared by mixing epoxy butyl oleate and epoxy fatty acid octyl ester in a weight ratio of 1:1.
[0070] The initiator is benzoyl peroxide; the cross-linking agent is a mixture of aluminum acetylacetonate and toluene diisocyanate in a weight ratio of 1:5; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:3; and the diluent is a mixture of ethyl acetate and acetone in a weight ratio of 3:1.
[0071] The preparation method of the polyacrylate pressure-sensitive adhesive comprises the following steps:
[0072] (R1), take soft monomer, hard monomer, functional monomer, difunctional epoxy acrylate, epoxy plasticizer, initiator, crosslinking agent, antioxidant and diluent according to weight parts and set aside;
[0073] (R2), mixing the initiator and the diluent evenly to obtain a diluted initiating solution, and dividing the solution into three portions, wherein the weight ratio of the first portion of the diluted initiating solution, the second portion of the diluted initiating solution and the third portion of the diluted initiating solution is 2:3:2;
[0074] (R3), mixing the soft monomer, the hard monomer, the functional monomer, the difunctional epoxy acrylate and the first diluted initiator solution evenly, and letting it stand for 3 minutes to obtain a prepolymer solution;
[0075] (R4), adding the second portion of the diluted initiating solution to the prepolymer solution at 75°C and 500 rpm for 3 hours, and keeping the temperature for 1 hour to obtain an intermediate product;
[0076] (R5) Add the third diluted initiator solution, epoxy plasticizer and crosslinking agent to the intermediate product at 85°C and 500 rpm, keep the mixture warm for 1 hour, then add antioxidant and mix well to obtain polyacrylate pressure-sensitive adhesive.
[0077] The heat shrinkable substrate layer is an oriented polystyrene film; the thickness of the heat shrinkable substrate layer is 39 μm, and the thickness of the polyacrylate pressure-sensitive adhesive is 10 μm.
[0078] The method for preparing the polyacrylate pressure-sensitive adhesive tape for improving the structural strength of a lithium battery comprises the following steps:
[0079] (S1), taking a heat shrinkable substrate layer and a polyacrylate pressure-sensitive adhesive, and setting them aside;
[0080] (S2), performing a surface corona treatment on the heat shrinkable substrate layer to obtain a surface corona heat shrinkable substrate layer;
[0081] (S3), heating the polyacrylate pressure-sensitive adhesive to 35° C., preheating for 20 min, filtering through a cartridge filter, and coating the polyacrylate pressure-sensitive adhesive on the corona surface of the surface corona heat shrinkable substrate layer to obtain a semi-finished product;
[0082] (S4), subjecting the semi-finished product to a multi-stage drying treatment and then winding it up to obtain a polyacrylate pressure-sensitive adhesive tape.
[0083] The filter pore size of the cartridge filter is 5 μm; in the step (S4), the temperatures of each stage of the multi-stage drying treatment are 80° C., 90° C., 100° C., and 90° C., respectively, and the drying time of each stage of the multi-stage drying treatment is 1 minute.
[0084] Example 3
[0085] A polyacrylate pressure-sensitive adhesive tape for improving the structural strength of a lithium battery, comprising a heat-shrinkable substrate layer and a polyacrylate pressure-sensitive adhesive coated on one side of the heat-shrinkable substrate layer;
[0086] The polyacrylate pressure-sensitive adhesive comprises the following raw materials in parts by weight:
[0087]
[0088] The soft monomer is a mixture of n-butyl acrylate and isooctyl acrylate in a weight ratio of 3:1; the hard monomer is a mixture of methyl methacrylate and styrene in a weight ratio of 5:2.
[0089] The functional monomer is a mixture of methacrylic acid and glycidyl methacrylate in a weight ratio of 2:5.
[0090] The bifunctional epoxy acrylate is prepared by mixing bisphenol A epoxy acrylate and novolac epoxy acrylate in a weight ratio of 1:9.
[0091] The epoxy plasticizer is prepared by mixing epoxy butyl oleate and epoxy fatty acid octyl ester in a weight ratio of 1:1.
[0092] The initiator is benzoyl peroxide; the cross-linking agent is a mixture of aluminum acetylacetonate and toluene diisocyanate in a weight ratio of 1:5; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:3; and the diluent is a mixture of ethyl acetate and acetone in a weight ratio of 3:1.
[0093] The preparation method of the polyacrylate pressure-sensitive adhesive comprises the following steps:
[0094] (R1), take soft monomer, hard monomer, functional monomer, difunctional epoxy acrylate, epoxy plasticizer, initiator, crosslinking agent, antioxidant and diluent according to weight parts and set aside;
[0095] (R2), mixing the initiator and the diluent evenly to obtain a diluted initiating solution, and dividing the solution into three portions, wherein the weight ratio of the first portion of the diluted initiating solution, the second portion of the diluted initiating solution and the third portion of the diluted initiating solution is 3:5:2;
[0096] (R3), mixing the soft monomer, the hard monomer, the functional monomer, the difunctional epoxy acrylate and the first diluted initiator solution evenly, and letting it stand for 5 minutes to obtain a prepolymer solution;
[0097] (R4), adding the second portion of the diluted initiating solution to the prepolymer solution at 80°C and 500 rpm for 2-3 hours, and keeping the temperature for 2 hours to obtain an intermediate product;
[0098] (R5) Add the third diluted initiator solution, epoxy plasticizer and crosslinking agent to the intermediate product at 90°C and 500 rpm, keep warm and react for 2 hours, then add antioxidant and mix well to obtain polyacrylate pressure-sensitive adhesive.
[0099] The heat shrinkable substrate layer is an oriented polystyrene film; the thickness of the heat shrinkable substrate layer is 43 μm, and the thickness of the polyacrylate pressure-sensitive adhesive is 11 μm.
[0100] The method for preparing the polyacrylate pressure-sensitive adhesive tape for improving the structural strength of a lithium battery comprises the following steps:
[0101] (S1), taking a heat shrinkable substrate layer and a polyacrylate pressure-sensitive adhesive, and setting them aside;
[0102] (S2), performing a surface corona treatment on the heat shrinkable substrate layer to obtain a surface corona heat shrinkable substrate layer;
[0103] (S3), heating the polyacrylate pressure-sensitive adhesive to 38° C., preheating for 20 min, filtering through a cartridge filter, and coating the polyacrylate pressure-sensitive adhesive on the corona surface of the corona heat shrinkable substrate layer to obtain a semi-finished product;
[0104] (S4), subjecting the semi-finished product to a multi-stage drying treatment and then winding it up to obtain a polyacrylate pressure-sensitive adhesive tape.
[0105] The filter pore size of the cartridge filter is 5 μm; in the step (S4), the temperatures of each stage of the multi-stage drying treatment are 80° C., 90° C., 100° C., and 90° C., respectively, and the drying time of each stage of the multi-stage drying treatment is 1 minute.
[0106] Example 4
[0107] A polyacrylate pressure-sensitive adhesive tape for improving the structural strength of a lithium battery, comprising a heat-shrinkable substrate layer and a polyacrylate pressure-sensitive adhesive coated on one side of the heat-shrinkable substrate layer;
[0108] The polyacrylate pressure-sensitive adhesive comprises the following raw materials in parts by weight:
[0109]
[0110] The soft monomer is a mixture of n-butyl acrylate and isooctyl acrylate in a weight ratio of 3:1; the hard monomer is a mixture of methyl methacrylate and styrene in a weight ratio of 5:2.
[0111] The functional monomer is a mixture of methacrylic acid and glycidyl methacrylate in a weight ratio of 2:3.
[0112] The bifunctional epoxy acrylate is prepared by mixing bisphenol A epoxy acrylate and novolac epoxy acrylate in a weight ratio of 1:9.
[0113] The epoxy plasticizer is prepared by mixing epoxy butyl oleate and epoxy fatty acid octyl ester in a weight ratio of 1:1.
[0114] The initiator is benzoyl peroxide; the cross-linking agent is a mixture of aluminum acetylacetonate and toluene diisocyanate in a weight ratio of 1:5; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:3; and the diluent is a mixture of ethyl acetate and acetone in a weight ratio of 3:1.
[0115] The preparation method of the polyacrylate pressure-sensitive adhesive comprises the following steps:
[0116] (R1), take soft monomer, hard monomer, functional monomer, difunctional epoxy acrylate, epoxy plasticizer, initiator, crosslinking agent, antioxidant and diluent according to weight parts and set aside;
[0117] (R2), mixing the initiator and the diluent evenly to obtain a diluted initiating solution, and dividing the solution into three portions, wherein the weight ratio of the first portion of the diluted initiating solution, the second portion of the diluted initiating solution and the third portion of the diluted initiating solution is 2:5:3;
[0118] (R3), mixing the soft monomer, the hard monomer, the functional monomer, the difunctional epoxy acrylate and the first diluted initiator solution evenly, and letting it stand for 5 minutes to obtain a prepolymer solution;
[0119] (R4), adding the second portion of the diluted initiating solution to the prepolymer solution at 78°C and 500 rpm for 2 hours, and keeping the temperature for 1 hour to obtain an intermediate product;
[0120] (R5) Add the third diluted initiator solution, epoxy plasticizer and crosslinking agent to the intermediate product at 86°C and 500 rpm, keep warm and react for 2 hours, then add antioxidant and mix well to obtain polyacrylate pressure-sensitive adhesive.
[0121] The heat shrinkable substrate layer is an oriented polystyrene film; the thickness of the heat shrinkable substrate layer is 40 μm, and the thickness of the polyacrylate pressure-sensitive adhesive is 12 μm.
[0122] The method for preparing the polyacrylate pressure-sensitive adhesive tape for improving the structural strength of a lithium battery comprises the following steps:
[0123] (S1), taking a heat shrinkable substrate layer and a polyacrylate pressure-sensitive adhesive, and setting them aside;
[0124] (S2), performing a surface corona treatment on the heat shrinkable substrate layer to obtain a surface corona heat shrinkable substrate layer;
[0125] (S3), heating the polyacrylate pressure-sensitive adhesive to 38° C., preheating for 18 min, filtering through a cartridge filter, and coating the polyacrylate pressure-sensitive adhesive on the corona surface of the corona heat shrinkable substrate layer to obtain a semi-finished product;
[0126] (S4), subjecting the semi-finished product to a multi-stage drying treatment and then winding it up to obtain a polyacrylate pressure-sensitive adhesive tape.
[0127] The filter pore size of the cartridge filter is 5 μm; in the step (S4), the temperatures of each stage of the multi-stage drying treatment are 80° C., 90° C., 100° C., and 90° C., respectively, and the drying time of each stage of the multi-stage drying treatment is 1 minute.
[0128] Comparative Example 1
[0129] The difference between this comparative example and Example 1 is:
[0130] The functional monomer is a mixture of methacrylic acid and maleic anhydride in a weight ratio of 2:4.
[0131] Comparative Example 2
[0132] The difference between this comparative example and Example 1 is:
[0133] The functional monomer is methacrylic acid.
[0134] Comparative Example 3
[0135] The difference between this comparative example and Example 1 is:
[0136] The polyacrylate pressure-sensitive adhesive comprises the following raw materials in parts by weight:
[0137]
[0138] That is, the polyacrylate pressure-sensitive adhesive of this comparative example does not contain difunctional epoxy acrylate, and difunctional epoxy acrylate is not added when preparing the polyacrylate pressure-sensitive adhesive.
[0139] Comparative Example 4
[0140] The difference between this comparative example and Example 1 is:
[0141] The difunctional epoxy acrylate is bisphenol A epoxy acrylate.
[0142] Comparative Example 5
[0143] The difference between this comparative example and Example 1 is:
[0144] The polyacrylate pressure-sensitive adhesive comprises the following raw materials in parts by weight:
[0145]
[0146]
[0147] That is, the polyacrylate pressure-sensitive adhesive of this comparative example does not contain epoxy plasticizer, and no epoxy plasticizer is added when preparing the polyacrylate pressure-sensitive adhesive.
[0148] Comparative Example 6
[0149] The difference between this comparative example and Example 1 is:
[0150] The epoxy plasticizer is prepared by mixing epoxy triglyceride and epoxy soybean oil in a weight ratio of 1:1.
[0151] Example 5
[0152] I. Take the polyacrylate pressure-sensitive adhesive tapes of Examples 1-4 and Comparative Examples 1-6, and test their 180° peeling force, initial tack, room temperature swelling multiple, 85°C swelling multiple and electrolyte resistance. The test method is as follows:
[0153] 180° peel strength: tested according to GB / T2792-2014 test method for peel strength of adhesive tapes, unit is g / 25mm.
[0154] Initial tack: The test is carried out in accordance with GBT4852-2002 pressure-sensitive adhesive tape initial tack test method (rolling ball method), and is expressed as the median (ball number) of the steel ball numbers of the rolling ball test results of the three samples during the formal test.
[0155] Swelling multiple at room temperature: take a pressure-sensitive tape and a diaphragm, measure the thickness of the pressure-sensitive tape and the diaphragm respectively with a micrometer thickness gauge, stick the pressure-sensitive tape to the diaphragm to form a sample, then soak the sample in a room temperature electrolyte for 0.5h, take out the sample and measure its thickness, calculate its swelling multiple, swelling multiple = (thickness of sample after immersion - thickness of diaphragm) ÷ thickness of pressure-sensitive tape, then take the average swelling multiple of the two groups of samples; wherein, the solute of the electrolyte is 1 mol / L lithium perchlorate trihydrate (CAS: 13453-78-6), and the solvent of the electrolyte is 1,2-propylene glycol carbonate (CAS: 108-32-7) and ethylene glycol dimethyl ether (CAS: 110-71-4) mixed in a weight ratio of 1:1.
[0156] 85℃ swelling multiple: take the pressure-sensitive tape and the diaphragm, respectively measure the thickness of the pressure-sensitive tape and the diaphragm with a micrometer thickness gauge, stick the pressure-sensitive tape to the diaphragm to form a sample, then soak the sample in 85℃ electrolyte for 4h, take out the sample and measure its thickness, calculate its swelling multiple, swelling multiple = (sample thickness after immersion - diaphragm thickness) ÷ pressure-sensitive tape thickness, then take the average swelling multiple of the two groups of samples; wherein, the solute of the electrolyte is 1 mol / L lithium perchlorate trihydrate (CAS: 13453-78-6), and the solvent of the electrolyte is 1,2-propylene glycol carbonate (CAS: 108-32-7) and ethylene glycol dimethyl ether (CAS: 110-71-4) mixed in a weight ratio of 1:1.
[0157] Electrolyte resistance: Take a pressure-sensitive tape and a separator, adhere the pressure-sensitive tape to the separator to form a sample, then soak the sample in a 40°C electrolyte for 48 hours, and observe whether the sample is debonded; wherein the solute of the electrolyte is 1 mol / L lithium perchlorate trihydrate (CAS: 13453-78-6), and the solvent of the electrolyte is 1,2-propylene carbonate (CAS: 108-32-7) and ethylene glycol dimethyl ether (CAS: 110-71-4) mixed in a weight ratio of 1:1.
[0158] The test results are shown in Table 1 below:
[0159]
[0160] II. The polyacrylate pressure-sensitive adhesive tapes of Examples 1-4 and Comparative Examples 1-6 were applied to cylindrical batteries, attached to the winding cores according to the same process to form semi-finished batteries, and assembled to obtain finished batteries according to the same process. The finished batteries were subjected to a roller test under the test conditions of 66 rotations per minute for 100 minutes. The voltage (V) and internal resistance (mΩ) of the finished batteries were tested, and the voltage change rate and internal resistance change rate were calculated. The test results are shown in Table 2 below:
[0161]
[0162] It can be seen from Tables 1 and 2 above that the special functional monomers, difunctional epoxy acrylates and epoxy plasticizers used in this application, under the action of initiators and cross-linkers, synergistically enhance the adhesion, electrolyte resistance, elasticity and flexibility of the pressure-sensitive adhesive, and are more conducive to adapting to the expansion deformation of the heat-shrinkable substrate layer, thereby improving the expansion effect of the heat-shrinkable substrate layer, and are more conducive to improving the structural strength of lithium batteries and improving the pass rate of cylindrical battery roller tests.
[0163] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.
Claims
1. A polyacrylate pressure-sensitive adhesive tape for improving the structural strength of a lithium battery, characterized in that: It includes a heat shrinkable base material layer, and a polyacrylate pressure-sensitive adhesive coated on one side of the heat shrinkable base material layer; The polyacrylate pressure-sensitive adhesive comprises the following raw materials in parts by weight: The functional monomer is a mixture of methacrylic acid and glycidyl methacrylate in a weight ratio of 2:3-5; The bifunctional epoxy acrylate is a mixture of bisphenol A epoxy acrylate and novolac epoxy acrylate in a weight ratio of 1:8-9, and the epoxy plasticizer is a mixture of epoxy butyl oleate and epoxy fatty acid octyl ester in a weight ratio of 1:
1.
2. The polyacrylate pressure-sensitive adhesive tape for improving the structural strength of a lithium battery according to claim 1, characterized in that: The soft monomer is at least one of n-butyl acrylate, isooctyl acrylate, and 2-ethylhexyl acrylate; the hard monomer is at least one of methyl methacrylate, methyl acrylate, and styrene.
3. The polyacrylate pressure-sensitive adhesive tape for improving the structural strength of a lithium battery according to claim 1, characterized in that: The initiator is at least one of benzoyl peroxide, diisopropylbenzene peroxide, azobisisobutyronitrile and dimethyl azobisisobutyrate; the crosslinking agent is aluminum acetylacetonate and / or toluene diisocyanate; the antioxidant is at least two of antioxidant 1010, antioxidant BHT and antioxidant 168; and the diluent is ethyl acetate and / or acetone.
4. A polyacrylate pressure-sensitive adhesive tape for improving the structural strength of a lithium battery according to any one of claims 1 to 3, characterized in that: The preparation method of the polyacrylate pressure-sensitive adhesive comprises the following steps: (R1), take soft monomer, hard monomer, functional monomer, difunctional epoxy acrylate, epoxy plasticizer, initiator, crosslinking agent, antioxidant and diluent according to weight parts and set aside; (R2), mixing the initiator and the diluent evenly to obtain a diluted initiating solution, and dividing the solution into three portions; (R3), mixing the soft monomer, the hard monomer, the functional monomer, the difunctional epoxy acrylate and the first diluted initiator solution evenly, and letting it stand for 3-5 minutes to obtain a prepolymer solution; (R4), adding the second diluted initiating solution to the prepolymer solution at 75-80°C and 300-500 rpm for 2-3 hours, and keeping the temperature for 1-2 hours to obtain an intermediate product; (R5) adding the third portion of the diluted initiating liquid, epoxy plasticizer and crosslinking agent to the intermediate product at a temperature of 85-90°C and a rotation speed of 300-500 rpm, keeping the reaction warm for 1-2 hours, and then adding an antioxidant and mixing evenly to obtain a polyacrylate pressure-sensitive adhesive.
5. The polyacrylate pressure-sensitive adhesive tape for improving the structural strength of a lithium battery according to claim 1, characterized in that: The heat shrinkable substrate layer is an oriented polystyrene film; the thickness of the heat shrinkable substrate layer is 37-43 μm, and the thickness of the polyacrylate pressure-sensitive adhesive is 8-12 μm.
6. A method for preparing a polyacrylate pressure-sensitive adhesive tape for improving the structural strength of a lithium battery as claimed in any one of claims 1 to 5, characterized in that: The steps include: (S1), taking a heat shrinkable substrate layer and a polyacrylate pressure-sensitive adhesive, and setting them aside; (S2), performing a surface corona treatment on the heat shrinkable substrate layer to obtain a surface corona heat shrinkable substrate layer; (S3), heating the polyacrylate pressure-sensitive adhesive to 35-40° C., preheating for 15-20 min, filtering through a cartridge filter, and coating the polyacrylate pressure-sensitive adhesive on the corona surface of the corona heat shrinkable substrate layer to obtain a semi-finished product; (S4), subjecting the semi-finished product to a multi-stage drying treatment and then winding it up to obtain a polyacrylate pressure-sensitive adhesive tape.
7. The method for preparing a polyacrylate pressure-sensitive adhesive tape for improving the structural strength of a lithium battery according to claim 6, characterized in that: The filter pore size of the cartridge filter is 3-5 μm; in the step (S4), the temperatures of each stage of the multi-stage drying treatment are 75-80°C, 88-92°C, 100°C, and 88-92°C, and the drying time of each stage of the multi-stage drying treatment is 1-2 minutes.
Citation Information
Patent Citations
Method for improving roller test passing rate of cylindrical battery
CN116470153A
Acrylate pressure-sensitive adhesive, oriented polystyrene expansion adhesive tape as well as preparation method and application thereof
CN113403007A
Electrolyte-solvent-resistant acrylate pressure-sensitive adhesive and preparation method thereof
CN113736398A
Embossed adhesive tape and preparation method thereof
CN115926670A